2020
DOI: 10.1182/blood.2019001645
|View full text |Cite
|
Sign up to set email alerts
|

Specific stimulation of T lymphocytes with erythropoietin for adoptive immunotherapy

Abstract: In adoptive T-cell immunotherapy of cancer, expansion and persistence of effector cells is a key determinant of response. We tested whether T lymphocytes could be rendered sensitive to erythropoietin (Epo) through ectopic expression of its wild-type receptor or a truncated form (EpoRm), which augments Epo signaling in erythrocyte progenitors. Both receptors could be expressed in human T lymphocytes; Epo ligation induced STAT5 phosphorylation, which was abrogated by nontoxic concentrations of the JAK1/2 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Recently, one study has discovered that engineered expression of the native form erythropoietin receptor (EpoR) or its truncated form (tEpoR) on the surface of CAR-Ts endows them with the ability to tune up their expansion, survival, and proliferation rate in response to erythropoietin ( 133 ). It has been evident that tEpoR exhibits supervisor characteristics, in comparison to EpoR, in terms of T-cell expansion, proliferation, and survival stimulation ( 133 ). Vinanica et al.…”
Section: Strategies For Overcoming the Hurdles Of Solid Tumor Car-t T...mentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, one study has discovered that engineered expression of the native form erythropoietin receptor (EpoR) or its truncated form (tEpoR) on the surface of CAR-Ts endows them with the ability to tune up their expansion, survival, and proliferation rate in response to erythropoietin ( 133 ). It has been evident that tEpoR exhibits supervisor characteristics, in comparison to EpoR, in terms of T-cell expansion, proliferation, and survival stimulation ( 133 ). Vinanica et al.…”
Section: Strategies For Overcoming the Hurdles Of Solid Tumor Car-t T...mentioning
confidence: 99%
“…Vinanica et al. generated tEpoR-expressing CD19-redirected CAR-Ts (tEpoR-CAR-Ts) and reported that these cells demonstrated pronounced ex vivo expansion and in vitro tumoricidal capacity against leukemic cells in the presence of erythropoietin ( 133 ). These results confirmed that the expression of either receptor does not negatively impact the functionality of the other ( 133 ).…”
Section: Strategies For Overcoming the Hurdles Of Solid Tumor Car-t T...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Blood, Vinanica et al explore a novel strategy to enhance the efficacy of adoptive T-cell therapy through the expression of an erythropoietin (Epo) receptor capable of delivering a signal that boosts the survival and function of chimeric antigen receptor (CAR) T cells. 1 Over the last 10 years, great strides have been made in the application of adoptive cellular therapy to treat malignant diseases. Through technological advances that enable the robust ex vivo expansion of T cells collected from peripheral blood as well as efficient redirection of T-cell specificity through CARs or engineered T-cell receptors (TCRs), it is now possible to manufacture and deliver sufficient numbers of leukemia-reactive T cells to treat, and even eradicate, chemotherapy refractory cancers.…”
mentioning
confidence: 99%